Functioning of Procedural Agreements in the Polish Legal System in Comparison with the Solutions Adopted by German Legislation - Modrzejewska, Klaudia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The history of consensual litigation in Polish criminal proceedings dates back to the 1990s. It is based on the assumption that the participants in the proceedings will come to an agreement on the resolution of the conflict, whichwill then be accepted by the court. This solution was most popular between 2010 and 2015. Since 2016, however, a change in attitudes towards consensual modes has been very noticeable. While the consensual method speeds upcriminal proceedings, opponents point to shortcomings - there are even calls to abandon their use in Poland. In the Federal Republic of Germany, on the otherhand, informal procedural agreements, called Absprachen, existed for several decades, and these agreements accelerated the course of proceedings. However, it was only decided to regulate this issue after several decades. In this article, I will characterise the reasons for the introduction and development of procedural agreements in the Republic of Poland and in the Federal Republic of Germany.